INFORMATION THREATS TO SMALL BUSINESS - Кудельський, Віталій (SWorldJournal, 2025)
The article is devoted to creating optimal conditions for the implementation of small business. The article reflects the necessity and need for ensuring information security for small business. The main causes of information threats in small enterprises